2016
DOI: 10.1108/ci-05-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

Innovation orientation in architectural firms

Abstract: Purpose Innovation is defined as the creation and adoption of changes that are new to an organisation or industry. The high probability of failure and the lack of innovation in the construction industry have highlighted the importance of innovation (both creation and adoption) as a business orientation. Although they are related to the construction industry, architectural firms receive little attention from an innovation perspective despite being perceived as important drivers of innovation. Thus, this paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 95 publications
(194 reference statements)
3
22
0
Order By: Relevance
“…The purposes of this pre-test were to evaluate the question structure and to ensure that the respondents recognised the purpose of the questions to establish validity (Dillman, 2000;Sekaran and Bougie, 2009). This pre-test approach is similar to that applied by Lai et al (2016), Kamaruddeen (2011) and in built environment research. Then, the questionnaire was improved by implementing adjustments such as shortening a question and avoiding technical terms.…”
Section: Innovation Orientations In Construction Companiesmentioning
confidence: 91%
See 2 more Smart Citations
“…The purposes of this pre-test were to evaluate the question structure and to ensure that the respondents recognised the purpose of the questions to establish validity (Dillman, 2000;Sekaran and Bougie, 2009). This pre-test approach is similar to that applied by Lai et al (2016), Kamaruddeen (2011) and in built environment research. Then, the questionnaire was improved by implementing adjustments such as shortening a question and avoiding technical terms.…”
Section: Innovation Orientations In Construction Companiesmentioning
confidence: 91%
“…Innovation orientations Hollenstein (2003) asserts that innovation should receive extra attention due to its complexity and that innovative actions should be comprehensively understood so that inconsistencies can be solved. Despite the extensive research on innovation, the fundamental concept of innovation remains uncertain (Lai et al, 2016;Damanpour and Schneider, 2009). To further address the inconsistencies in innovation studies, Fagerberg (2009, p. 9) asks, "If A for the first time introduces a particular innovation in one context, while B later introduces the same innovation in another, would we characterize both as innovators?"…”
Section: Innovation Orientations In Construction Companiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it would not be surprising if BIM technology received a slow response from the industry players (Rogers et al, 2015, Liao et al, 2017. At the same time, innovations in the construction industry are not all the same, and each innovation has different influencing factors and outcomes (Lai et al, 2016). Kamal et al (2016) showed that some firm characteristics have different impacts on a firm's adoption of innovation.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many research studies that have applied the BIM and ICT (Information and Communications Technologies) technologies in the construction industry [29][30][31]. However, various causes, such as the culture, workforce, and system of the organization, act as a serious impediment to BIM application [32][33][34][35]. In particular, construction companies are reluctant to adopt a wide range of high-tech digital technologies due to their complexity, high risk, and conservatism.…”
mentioning
confidence: 99%